Simultaneously collecting coding and non-coding phylogenomic data using homemade full-length cDNA probes, tested by resolving the high-level relationships of Colubridae - Li, JiaXuan; Liang, Dan; Zhang, Peng (Frontiers in Ecology and Evolution, 2022)
Resolving intractable phylogenetic relationships often requires simultaneously analyzing a large number of coding and noncoding orthologous loci. To gather both coding and noncoding data, traditional sequence capture methods require custom-designed commercial probes. Here, we develop a cost-effective sequence capture method based on homemade probes, to capture thousands of coding and noncoding orthologous loci simultaneously, suitable for all organisms. This approach, called "FLc-Capture", synthesizes biotinylated full-length cDNAs from mRNA as capture probes, eliminates the need for costly commercial probe design and synthesis. To demonstrate the utility of FLc-Capture, we prepared full-length cDNA probes from mRNA extracted from a common colubrid snake. We performed capture experiments with these homemade cDNA probes and successfully obtained thousands of coding and noncoding genomic loci from 24 Colubridae species and 12 distantly related snake species of other families. The average capture specificity of FLc-Capture across all test snake species is 35%, similar to the previously published EecSeq method. We constructed two phylogenomic data sets, one including 1,075 coding loci (~817,000 bp) and another including 1,948 noncoding loci (~1,114,000 bp), to study the phylogeny of Colubridae. Both data sets yielded highly similar and well-resolved trees, with 85% of nodes having > 95% bootstrap support. Our experimental tests indicated that FLc-Capture is a flexible, fast, and cost-effective sequence capture approach for simultaneously gathering coding and noncoding phylogenomic data sets to study intractable phylogenetic questions. We anticipate that this method can provide a new data collection tool for the evolutionary biologists working in the era of high-throughput sequencing.